Design of an agent-based model to simulate urban growth at Corredor del Henares (Region of Madrid) - Carolina Cantergiani; Montserrat Gómez Delgado (Boletín de la Asociación de Geógrafos Españoles)
Due to urban sprawl impact over the planet and the population, the use of simulation techniques that generate scenarios regarding the evolution of those systems is imperative. Agent-based models (ABM) are presented as a promising alternative. ABM is a dynamic cellular model based on decision rules guided by the behaviour of agents. In the present work, we propose the design of an ABM to simulate urban growth in `Corredor del Henares´ (Community of Madrid, Spain), considering its urban dynamics and the main involved agents, as well as their particular behaviour and the available data. The main goal is to have a solid conceptual design in order to prove, in a short time, that ABM can be an alternative tool to simulate urban growth at a sub-regional scale.